Repurposing drugs targeting the P2X7 receptor to limit hyperinflammation and disease during influenza virus infection. (19th August 2019) - Rosli, Sarah; Kirby, Francis J.; Lawlor, Kate E.; Rainczuk, Kate; Drummond, Grant R.; Mansell, Ashley; Tate, Michelle D.
Abstract : Background and Purpose: Severe influenza A virus (IAV) infections are associated with damaging hyperinflammation that can be fatal. There is an urgent need to identify new therapeutic agents to treat severe and pathogenic IAV infections. Repurposing of drugs with an existing and studied pharmacokinetic and safety profile is a highly attractive potential strategy. We have previously demonstrated that the NLRP3 inflammasome plays time‐dependent roles during severe IAV infection with early protective responses and later dysregulation leading to excessive inflammation, contributing to disease severity. Experimental Approach: We tested two existing drugs, probenecid and AZ11645373, to target P2X7 receptor signalling and dampen NLRP3 inflammasome responses during severe IAV infection. In vitro, the drugs were assessed for their ability to limit NLRP3 inflammasome‐dependent IL‐1β secretion in macrophage cultures. In vivo, their effects were assessed on hyperinflammation and disease during severe IAV infection in C57BL/6 mice. Key Results: Treatment of macrophages with probenecid or AZ11645373 in vitro diminished NLRP3 inflammasome‐dependent IL‐1β secretion. Intranasal therapeutic treatment of mice displaying severe influenza disease with probenecid or AZ11645373 reduced pro‐inflammatory cytokine production, cellular infiltrates in the lung, and provided protection against disease. Importantly, these drugs could be administered at either early or late stage of disease and provide therapeutic efficacy. Conclusions and Implications: Our study demonstrates that the anti‐inflammatory drugs probenecid and AZ11645373, which have documented pharmacokinetics and safety profiles in humans, are effective at dampening hyperinflammation and severe influenza disease providing potentially new therapeutic strategies for treating severe or pathogenic IAV infections.